Video Editing Training Utilizing Capcut Application at SMKM 7 East Tebet: Pelatihan Editing Video Menggunakan Aplikasi Capcut di SMKM 7 Tebet Timur - Oktarina Heriyani; Faldy Irwiensyah; Rifky; Dan Mugisidi; M. Mujirudin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
The significance of video editing skills in conveying messages in the digital era has prompted the implementation of a training program at SMKM 7 Tebet Timur, focusing on the utilization of the CapCut application. This topic was selected to address the challenge of insufficient understanding and skills among students in applying video editing techniques, aligning with contemporary demands in visual communication. The training method encompassed material preparation, theoretical presentation, demonstration, hands-on practice, evaluation, and discussion. The evaluation revealed a notable improvement in the students' understanding and skills post-training, with average scores experiencing significant increments. The conclusion underscores the importance of a holistic approach in multimedia training and recommends further collaboration with higher education institutions. The training outcomes also fostered positive relations between SMKM 7 Tebet Timur and FTII UHAMKA. This training makes a tangible contribution to preparing students to meet the demands of an increasingly visually connected professional world.